Negative associations of ideal family size achievement with hypertension, obesity and maternal age in women with and without polycystic ovary syndrome. (21st April 2022) - Tay, Chau Thien; Loxton, Deborah; Khomami, Mahnaz Bahri; Teede, Helena; Joham, Anju E.
Abstract: Objective: To investigate lifetime reproductive outcomes and the relationship of ideal family size (IFS) achievement with metabolic, psychiatric and reproductive history in women with and without polycystic ovary syndrome (PCOS). Design: Cross‐sectional. Patient(s): A total of 9034 women with ( n = 778) and without self‐reported PCOS ( n = 8256) born between 1973 and 1978 in the Australian Longitudinal Study on Women's Health. Measurements: Self‐reported IFS achievement and total number of live births. Results: Women with and without PCOS aspired for similar IFS. Compared with women without PCOS, significantly less women with PCOS achieved their IFS (53.08% vs. 60.47%, p < 0.001). Higher proportion of women with PCOS did not achieve a live birth (37.15% vs. 31.64%, p = 0.002) and their median total number of live births was also lower (1 vs. 2, p < 0.001) than women without PCOS. After controlling for sociodemographic factors, negative associations were observed between IFS achievement and PCOS status, various metabolic, psychiatric and reproductive history. However, only hypertension (adjusted odds ratio [OR]: 0.82, 95% confidence interval [CI]: 0.67–1.00), obesity (adjusted OR: 0.79, 95% CI: 0.69–0.90), history of in vitro fertilisation use (IVF) (adjusted OR: 0.49, 95% CI: 0.38–0.63) and maternal age at first childbirth (adjusted OR: 0.92, 95% CI: 0.91–0.93) remained inversely associated with achievement of IFS in further multivariable regression models. Conclusion: Metabolic conditions and reproductive history of maternal age at first childbirth and history of IVF use, but not psychological conditions, were associated with reduced odds of achieving IFS. Early family planning/initiation and optimisation of metabolic health may help to improve reproductive outcomes.